Strategies for sustaining business vitality in international wholesale and retail trade : the case of a small company in Singapore - Avni Dhanvantry Shah (2010)
The wholesale and retail trade is an important contributor to Singapore’s GDP. Small medium enterprises (SMEs) in this industry make up 32% of the total SMEs in Singapore. However, the large number of cessations of companies in the wholesale and retail trade attests to the importance of understanding how SMEs can survive in this competitive industry.